Impact of Pharmacological Competencies on the Reduction of Medication Errors in Critical Care Units - Plenza, Ayelén Estefanía; Gabini, Sebastián; Ponti, Liliana (SCT Proceedings in Interdisciplinary Insights and Innovations, 2025)
The use of drugs to treat disease and relieve pain has historical roots that evolved significantly over time, especially in the 20th century, when pharmacology became a central discipline in healthcare and nursing. This practice, although essential for patient recovery, especially in high-intervention settings such as intensive care units, is prone to errors that can have serious consequences for patients. The National Coordinating Council for Medication Error Prevention (NCC MERP) has developed error classification and analysis tools, emphasizing that errors are often preventable and multifactorial, highlighting the importance of nursing staff pharmacological knowledge. Several studies have identified the causes and consequences of medication errors. In Ecuador, errors were related to high patient demand, non-compliance with schedules and poor administration technique. In Cuba, a general mastery of medications was observed, but a deficiency in the recognition of adverse reactions. In Spain, pharmacovigilance showed low rates of spontaneous reporting of adverse events, attributable to insufficient training in pharmacology. In critical care units, the most common errors included administration, dilution and dosing techniques, exacerbated by pressure of care and communication problems. In this context, nursing plays a crucial role as it is at the end of the pharmacotherapeutic process, acting as the last barrier to prevent errors from reaching the patient. This study in an Intensive Care Unit in Rosario seeks to delve into this problem, highlighting its impact on patients and on the professional development of nursing staff, with the aim of providing practical and theoretical solutions